INCREASING STUDENTS’ VOCABULARY BY USING COMIC STRIPS : (A Study Conducted at SMP Anugrah Tondano) - Korompot, Rahman; Olii, Sanerita T.; Rorimpandey, Rinny (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This research aims at finding out whether the use of comic strips could increase the students’ vocabulary or not. In conducting this research, quantitative method with pre-experimental design (one group pre-test and post-test) is used. This research is carried out at SMP Anugrah Tondano in which the subject of this research is 8 first-grade students of SMP Anugrah Tondano. The data are collected through matching test and are analyzed by using the mean score formula. The findings show that the mean score of the post-test (85.6) is higher than the pre-test score (58.1). It indicates that Comic Strips is effective way to increase students’ vocabulary. So, it can be concluded that the use of Comic Strips as a technique is effective to increase the students’ vocabulary. Since this study is conducted in the pre-experimental design, further studies with the experimental design are expected to show the effectiveness of using comic strips in English Language Teaching.